KETIDAKPASTIAN ATAS KEKUATAN HUKUM PUTUSAN HOMOLOGASI TERHADAP PENYITAAN ASET PERUSAHAAN YANG DIDUGA HASIL DARI TINDAK PIDANA PENCUCIAN UANG - Pratama, Agung; Ratnawati, Elfrida; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Ensiklopedia of Journal, 2025)
Abstract: This paper aims to analyze the uncertainty over the legal force of homologation decisions on the confiscation of company assets suspected of being the proceeds of money laundering crimes, focusing on the main issues related to legal uncertainty in the context of the implementation of homologation decisions (amicable agreements in bankruptcy proceedings) and how it affects the confiscation of assets suspected of being involved in money laundering crimes. This journal explores the conflict between bankruptcy law and criminal law, particularly in situations where the assets of the company involved in the homologation are suspected to be proceeds of crime. This research uses the normative method, namely legislation. The results show that the homologation decision needs to take precedence before the process of confiscating company assets suspected of originating from money laundering crimes. This is because the process of criminal confiscation events that occur against company assets suspected of being the proceeds of money laundering has clashed with the principle of Ultimum Remedium.Keywords: Bankruptcy Law, TPPU, Homologation.